Risk Management Based on Lā Ḍarar wa Lā Ḍirār in Sharia Home Financing - Kurnaemi Anita; Wahyuddin Abdullah; Sumarlin, Sumarlin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyze and elaborate on the concept of risk management based on lā ḍarar wa lā ḍirār in Sharia Home Financing at PT Wahana Persada Indonesia, one of the Sharia Property Developers. The research employs a qualitative method with a grounded theory methodology approach. Data were collected through in-depth interviews with relevant organizational stakeholders, observations, and document analysis. The findings reveal that the risk management concept implemented by PT Wahana Persada Indonesia involves a step-by-step process comprising risk qualification, risk identification, and risk control as part of the application of lā ḍarar wa lā ḍirār. Risk management strategies are conducted within the framework of Islamic legal maxims (qawā‘id fiqhiyyah) and are constructed into two derived principles, namely al-ḍarar yudfa‘ bi qadri al-imkān (harm should be removed as much as possible) and al-ḍarar yuzāl (harm must be eliminated), which serve as analytical tools. The findings of this study can serve as input for risk management regulations in Islamic financial institutions or other Sharia-compliant developers by integrating risk management strategies with Sharia values.